The Position of Heterodox Economics in Economic Science - Matoušková, Eleonóra (Public Finance Quarterly, 2021)
In economic science dominate orthodox economics (mainstream economics respectively neoclassical economics). Despite its numerous intellectual failures, orthodox economics continue to prevail in teaching at universities. A certain alternative to orthodox economics is heterodox economics, which consists of three groups of theoretical approaches, represented by the Left-wing heterodoxy and Neo-Austrian school (we include them together in the Old heterodoxy) and the New heterodoxy. The objective of this article is to define the differences between orthodox economics and heterodox economics, to find common features of individual heterodox approaches and identify substantial differences between them and also highlight the relevance of these heterodox approaches from the point of view of the challenges we are facing today. A common characteristic of heterodoxy is the rejection of orthodoxy, especially its research methods. Heterodox economists reject the axiom that individuals are always rational, the concept of ‘homo economicus’, the application of a formal-deductive approach, the use of mathematical methods in cases that are not appropriate for this, and access from a closed system position. Heterodoxy is a very diverse theoretical tradition, and there are differences not only between the Left-wing heterodoxy, Neo-Austrian school and New heterodoxy, but also within these heterodox groups. They differ on specific topics they deal with and proposed solutions to socio-economic problems.